International Advertising Strategy: Standardization or Adaptation? - Gaurav, Kunal (Indian Journal of Marketing, 2008)
Advertising is one of the most critical elements of communication mix of a company and it plays very important role in building brand image. The power of successful transfer of promotion campaign around the globe is a considerable advantage of a globally oriented company in term of competitiveness. As world is witnessing globalization where business is expanding beyond the national boundaries, companies started viewing the whole world as a single market. Multinational companies very often face the trouble of whether to, up to what extent and in which way advertising should be adopted or changed before deploying a particular advertising message in the diverse international market. That is, under what situation international advertising campaign should be standardized or customized, and up to what extent? This is a Conceptual paper which aims at explaining rationale behind a particular approach of international advertising. This paper also talks about different situations which make a particular advertising approach successful across the countries.